A consultation and simulation system for product color planning based on interactive genetic algorithms. Issue 5 (30th March 2012) - Hsiao, Shih‐Wen; Hsu, Chiao‐Fei; Tang, Kai‐Wei
<x xml:space="preserve">Abstract</x> In the early stage of a design process, it is important to create numerous and varied possible color plans for the target consumer group. These color plans help individual designers quickly find a few good color design schemes and give the design team ideas for brainstorming. The color plan of a product consists of the color combinations of its components and decorative patterns, which strongly influence the feelings of customers and thus their desire to purchase. However, very few studies have discussed these issues. In this study, a consultation and simulation system for product color planning that helps designers obtain the optimal color planning for components and decorative patterns of a product is proposed. This system includes two parts: one uses the interactive genetic algorithm to establish a creative evolutionary system that can interact with a designer to explore novel design schemes; the other extends the boundary extract algorithm to establish a color simulation system that can apply colors to the areas of product components and decorative patterns for color simulation. Finally, a case study of color planning for a motorcycle model is used to verify the feasibility of the proposed system. © 2012 Wiley Periodicals, Inc. Col Res Appl, 38, 375–390, 2013